Sarcocystosis with thin Wall Cyst in Cardiac Muscle of Bullock : A Case Report - Sonwane, Suvarna R.; Ingole, R. S.; Hedau, Madhuri; Ingole, D. K. (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
Sarcocystosis is a parasitic zoonoses caused by species of Sarcocystis, an intracellular protozoan parasite in the phylum Apicomplexa. In cattle Sarcocystis is mainly caused by Sarcocystis cruzi, Sarcocystis hominis and Sarcocystis hirsute. Bovine sarcocystosis caused by Sarcocystis cruzi mainly by ingesting the protozoan eggs through feed. The infection is mainly characterized by cyst formation in muscular tissue. Heart, diaphragm and skeletal muscles are the preferred locations for Sarcocystis spp in intermediate host and are more prevalent in adult animals (Rao and Hafeez, 2002). Bovine Sarcocystis results in weight loss, anorexia, decreased milk production, anemia, and prostration and in fatal cases often culminating in death of animals (Dafedar et al., 2011). The significance of bovine Sarcocystis infection prompted us to put the present case on record.